Human hair-derived hollow carbon microfibers for electrochemical sensing. (October 2016) - Pramanick, Bidhan; Cadenas, Lorena Berrón; Kim, Dong-Min; Lee, Wonchul; Shim, Yoon-Bo; Martinez-Chapa, Sergio O.; Madou, Marc J.; Hwang, Hyundoo
Abstract: Glassy carbon has been widely used for various applications including electrochemical sensors and energy storage devices. Here we introduce a novel way to fabricate glassy carbon microfibers based on human hairs. The coaxial structure of hair shafts results in long hollow glassy carbon structures upon pyrolysis at 900 °C in a N2 atmosphere. The morphology of human hair samples before and after pyrolysis was characterized using scanning electron microscopy. The chemical composition of natural and pyrolyzed human hairs was also characterized using Raman spectroscopy and energy-dispersive X-ray spectroscopy. Screen printed carbon electrodes were modified with the hair-derived carbons and applied for electrochemical sensing of dopamine and ascorbic acid. The hair-derived carbons significantly improved the performance of the electrochemical sensors compared to the unmodified sensors. This method provides an easy, simple, and inexpensive way to fabricate hollow 3D glassy carbon microelectrodes.